Cementless Extensive Porous-Coated Mono-block Long Stem Hemiarthroplasty versus Proximal femoral Nail for Unstable Osteoporotic Intertrochanteric Fracture in the Elderly Patients: a retrospective study - Dündar, Abdulrahim; Ipek, Deniz (International Journal of Scientific Research and Management (IJSRM), 2022)
Introduction: The treatment for unstable intertrochanteric fractures in the elderly patient has always been controversial. The aim of this study was to compare the outcome of porous coated cementless mono-block long stem hemiarthroplasty (CPH) and proximal femoral nail (PFN) on unstable intertrochanteric femoral fracture in the elderly patients. Methods: From March 2017 and March 2020, 132 elderly patients with unstable femoral intertrochanteric fractures were treated by CPH or PFN. 73 patients were treated using proximal femoral nail (PFN) and 59 were treated using hemiarthroplasty (CPH). Bleeding amount, weight training time, hospitalization time, Harris scores, one-year mortality, pre-existing disease and postoperative complications were analyzed.Results: The average follow-up time was 23.2 months in the CPH group and 22.9 months in the PFN group. No significant differences was found between the two groups in terms of demographic data. There was no significant differences between the two groups regarding the ASA score, pre-existing disease, postoperative complications, and revision surgery. The mean operation time and the average amount of blood loss were significantly higher in the CPH group (p